Pendampingan Pembuatan Sertifikasi Halal Produk UMKM di Desa Banjaragung, Kecamatan Bareng - Faiza Aulia Novadinastia; Nurul Azizah (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Assistance in Making Halal Certification for food and beverage MSME products in Banjaragung Village, Bareng District, Jombang Regency aims to increase understanding of the importance of halal certification to improve the quality of MSME products, increase the selling value of MSME products, and increase the interest and comfort of potential consumers of products from MSME players in Banjaragung Village. The method of implementing this community service activity is socialization and assistance in applying for halal certification for free through SiHalal with the Sehati 2023 program. The results of this community service activity are (1) MSMEs understand the importance of halal certification, (2) MSMEs understand the procedures for halal certification, and (3) The issuance of halal certification for Banjaragung Village MSME players. Thus, consumer buying interest and consumer confidence are expected to increase with the halal label. In addition, it is also expected to increase product sales and community welfare in Banjaragung Village, Bareng District, Jombang Regency.